EVALUATING THE EFFECTIVENESS OF TARGETED THERAPY IN THE TREATMENT OF PATIENTS WITH GRANULOMATOSIS WITH POLYANGIITIS - Berdieva D. U. (Modern American Journals, 2025)
In recent years, several recommendations for the treatment of granulomatosis with polyangiitis (GPA) have been developed by major expert groups, including EULAR, ERA-EDTA, the European Vasculitis Society, the British Society for Rheumatology, and the British Association of Rheumatologists. Due to the clinical heterogeneity and the severity of prognosis, the management and treatment strategies for patients with GPA are often challenging. The necessity of early diagnosis of GPA is driven by the need to initiate aggressive therapy as early as possible. The main goal of therapy is to suppress the underlying immunopathological reactions in order to achieve complete remission. This article presents an evaluation of the effectiveness of targeted therapy in the treatment of granulomatosis with polyangiitis.
Keywords: Granulomatosis with polyangiitis, treatment.